Program Aplikasi Data Penjualan Berbasis Web Pada CV. Gading Cipta Mukti - Rena Saputri; Yakub (ALMUISY: Journal of Al Muslim Information System, 2024)
To support all of that, it is necessary to develop a system that must be sufficient. In addition, the information on the number of goods available for sale is also not informative, so many requests are delayed due to a lack of stock information that should still be there, but the goods cannot be found. In order for an effective and efficient input process to occur and good information dissemination to the owner and admin regarding information on stock and prices, it is necessary to have a system to assist this process. To facilitate the sales transaction process effectively and efficiently, a web-based sales application program was created using PHP and MySQL. With this system, the transaction process which was originally carried out manually, has now become systemized so that the transaction process can run more effectively and efficiently, information on the availability of available goods can be more informative for the admin because the stock is up to date and with this system, the revenue recap process which was originally still manual from transactions, is now more systemized and can be printed according to a certain period of time by the admin